(untitled) (World Science, 2025)
The Zit Emba dam (in the far north-east of Algeria) was impounded in 2001. With a capacity of 117,39 hm3, siltation is monitored solely by bathymetric surveys (2004 and 2014). The first company obtained a volume of silt of 0,8 hm3. The second survey estimated the amount of silt at 4,7 Hm3. However, the silt removed is estimated at 20% of the total silt. As a result, 5,6 Hm3 of sediment landed in the reservoir. In other words, a specific degradation equal to 1300 t/km2/year. However, this siltation monitoring does not allow us to locate the most degraded input zones. We therefore chose the USLE (Universal Soil Loss Equation) to quantify and spatialise hydric erosion in the watershed. To compare the bathymetric measurements with the soil losses obtained by the USLE, we subtracted the equivalent of silt transport (25%), giving a ratio of average annual soil losses (289.103 t/year) to estimated average annual solid transport (485.103 t/year) equal to 60%. This approach enabled us to validate the results obtained by the model, and to locate and quantify the degraded and very degraded surfaces (17,5 km2), or 3.6% of the total surface area of the watershed. They produce 77.103 t/year, representing 26% of annual soil losses. Developing these vulnerable areas will inevitably extend the lifespan of the Zit Ema dam, at a lower cost.